Direct Deposition of Crystalline Aragonite in the Controlled Biomineralization of the Calcareous Tubeworm - Chan, Vera B. S.; Toyofuku, Takashi; Wetzel, George; Saraf, Laxmikant; Thiyagarajan, Vengatesen; Mount, Andrew S. (Frontiers in Marine Science, 2015)
Although space delineation is a well-accepted requirement for biologically controlled biomineralization, the actual location of the mineralizing compartment within marine invertebrates has only recently been determined. We observed that the biomineralization was compartmented within the collar region of the metamorphosing larvae of Hydrodies elegans at its earliest possible time, i.e. at the post-metamorphic stage. We have also found that these highly regulated compartments contained aragonite crystals, as detected by EBSD and confirmed by electron diffraction TEM. Within these compartments, the metamorphosed larvae maintained a pH 9, at the pKa for CaCO3 formation. This model describes how biomineralization is a space delineation event in which calcium carbonate formation is an intracellular phenomenon.